Incorporating Taxes and Duties in Supply Chain Design between Tax Payers and Tax Administration in Iraq - Arshed Makki Rashid; Haider Omran Seher; Ali Ghanim Shakir Baghdadi (International Journal of Supply Chain Management, 2019)
This research tries to breach the forbidden laws of the judiciary by the help of empirical research of the Iraqi tax courts. So challenges the tax judiciary is going to face while the encompassing the disputes between tax payers and tax administration is going to be measured by two-stage Data Envelopment Analysis technique with bootstrapping. Thus it had measured the disputes of Iraqi courts. This research had also taken the benefit of a distinctive article of this division of the Iraqi judiciary where the judges are appointed for short term of periods and can last to exercise an peripheral profession to measure the influence the costs of opportunities and the conflicts between the payers and the administration including the conduct of the judges. The general result had confirmed that the judges exploit efficacy.